A photonic integrated circuit-based erbium-doped amplifier - Liu, Yang; Qiu, Zheru; Ji, Xinru; Lukashchuk, Anton; He, Jijun; Riemensberger, Johann; Hafermann, Martin; Wang, Rui Ning; Liu, Junqiu; Ronning, Carsten; Kippenberg, Tobias J. (Science, 2022)
Erbium-doped fiber amplifiers revolutionized long-haul optical communications and laser technology. Erbium ions could provide a basis for efficient optical amplification in photonic integrated circuits but their use remains impractical as a result of insufficient output power. We demonstrate a photonic integrated circuit-based erbium amplifier reaching 145 milliwatts of output power and more than 30 decibels of smallsignal gain-on par with commercial fiber amplifiers and surpassing state-of-the-art III-V heterogeneously integrated semiconductor amplifiers.We apply ion implantation to ultralow-loss silicon nitride (Si3N4) photonic integrated circuits, which are able to increase the soliton microcomb output power by 100 times, achieving power requirements for low-noise photonic microwave generation and wavelength-division multiplexing optical communications. Endowing Si3N4 photonic integrated circuits with gain enables the miniaturization of various fiber-based devices such as high-pulse-energy femtosecond mode-locked lasers.
CRIS-Team Scopus Importer:2023-04-20